Initiated into Subordination. On Joyce Carol Oates`s "I`ll Take You There" = Inicjacja do podległości. O "Zabiorę cię tam" Joyce Carol Oates - Zawadzka, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article proposes a sociological reading of the novel "I`ll Take You There" by Joyce Carol Oates. Though the book can be classified as an initiation novel, it also constitutes an accusation of the very procedure of initiation as forcing individuals to agree and adapt to unfair social mechanisms. The context of the protagonist`s struggles is provided by the social structure of the early-1960s United States, with its inherent misogyny, anti-Semitism, racism and classism.
Keywords: Oates, Joyce Carol (1938- ); "I`ll Take You There"; anti-Semitism; racism; misogyny; antysemityzm; rasizm; mizoginizm